IMPLEMENTASI PROMOSI DESA WISATA ROTAN TRANGSAN KABUPATEN SUKOHARJO MELALUI FILM DOKUMENTER SEJARAH - Yusana Sasanti Dadtun; Destian Dewantoro; Aulya Zahra Kharismanty; Bambang Ratri Subagya; Dania Meisah Putri; Diana Ema Fitriani; Evi Lia Novita Sari; Galuh Amalia Kus Furi; Ira Monikha; Lia Kurniawati; Ranya Andien Aqmarina (Jurnal Abdi Insani, 2023)
Trangsan Village, Sukoharjo Regency, Central Java Province, is the area with the largest rattan craft producing industry in Central Java Province and the second in Indonesia. The Trungsan Rattan Tourism Village has its own charm, namely specific, historical uniqueness and its main attraction is industry-based. There is a lot of potential offered by the Trungsan Rattan Tourism Village area, but there are important things that have not been optimized, especially regarding tourism promotion. This community service activity aims to explore the tourism and rattan industry potential in Trangsan Village as well as management, promotion and community role activities in optimizing the Trangsan Rattan Tourism Village. This activity was carried out by collecting data in the form of interviews, literature studies, and observations at the activity location. Interviews were conducted with the Head of Trangsan Village and historical sources, namely Mr. Warsino and Mr. Marjono, as well as several rattan craftsmen in Trangsan Village. The results and discussion in this paper are the potential for developing the Rattan Trungsan Tourism Village, Gatak District, Sukoharjo Regency, which is a tourist destination. Management of tourism potential and the rattan industry through "Grebeg Penjalin" activities. The marketing plan carried out by the Trangsan Village is in accordance with the target market, namely carrying out promotions through social media and distributing leaflets to schools in Sukoharjo Regency. The design of the documentary film entitled "History of the Rattan Trangsan Tourism Village" with the theme of the History of the Tourist Village is divided into two versions, namely the full version which has a duration of 12 minutes and the short version (trailer version) which has a duration of 1-2 minutes. In this film, video interviews were produced in the form of a documentary by resource persons including rattan craft pioneers, MSMEs, and the head of Trangsan Village.